Sphingosine-1-phosphate induces development of functionally mature chymase-expressing human mast cells from hematopoietic progenitors - Price, Megan M. (The Federation of American Societies for Experimental Biology, 2009)
Mast cells (MCs) play a critical role in both acute and chronic inflammation and mature in peripheral tissues from bone marrow-derived progenitors that circulate in the blood as immature precursors. MCs developed from cord blood-derived progenitors cultured with stem cell factor (SCF) alone express intragranular tryptase (MC(T)s), the phenotype predominant in the lung. MC progenitors are likely to encounter the serum-borne bioactive sphingolipid metabolite, sphingosine-1-phosphate (S1P), during migration to target tissues. S1P accelerated the development of cord blood-derived MCs (CB-MCs) and strikingly increased the numbers of MC-expressing chymase. These MCs have functional FcεRIs, and similar to skin MC(TC)s that express both tryptase and chymase, also express CD88 and are activated by anaphylatoxin C5a and the secretagogue compound 48/80. S1P induced release of IL-6, a cytokine known to promote development of functionally mature MC(TC)s, from cord blood cultures containing adherent macrophages, and from highly purified macrophages, but not from macrophage-depleted CB-MCs. In contrast, S1P stimulated secretion of the chemokine, monocyte chemoattractant protein 1 (MCP-1/CCL2), from these macrophage-depleted and purified CB-MCs. These results suggest crucial roles for S1P in regulating development of human MCs and their functions and reveal a complex interplay between macrophages and MC progenitors in the development of mature human MCs.—Price, M. M., Kapitonov, D., Allegood, J., Milstien, S., Oskeritzian, C. A., Spiegel, S. Sphingosine-1-phosphate induces development of functionally mature chymase-expressing human mast cells from hematopoietic progenitors.